Potenciais microRNAs circulantes como biomarcadores de Leucemia Mieloide Crônica - Fase Crônica: recém diagnosticada e tratada com mesilato de imatinibe - Ferreira, Letícia Antunes Muniz [UNESP] (2016)
Chronic Myeloid Leukemia (CML) is a myeloproliferative disorder, result of clonal expansion of hematopoietic stem cells progenitor, characterized by BCR-ABL1 fusion gene as a result of reciprocal translocation t (9;22) (q34;q11) called chromosome Philadelphia (Ph). With the acquired knowledge about the BCR-ABL1 action mechanisms has been possible to develop a target specific drug very efficient. However, some patients have refractoriness to treatement or develop mutations which induce drug resitence and also CML leukemia stem cells can be resistant to treatment. Such factors renewed interest in the pathophysiology of CML, including the role of microRNAs (miRNAs). miRNAs are small non-coding RNAs (ncRNAs) that control the gene expression, and play an important role in cancer development and progression. The aims of this study were to identify a global expression profile of circulating miRNAs in patients CML-CP (Chronic Myeloid Leukemia – chronic phase) newly diagnosed and CML-CP treated with imatinib, correlating the profile of miRNA expression between the two groups of patients, and finally, detect networks of interactions between miRNAs and BCR-ABL1. RT-qPCR array was used for analysis of 768 miRNAs. The results indicated that the 768 miRNAs analyzed, 43 miRNAs characterize CML-CP newly diagnosed versus CML-CP treated with imatinib. Of these, 39 miRNAs are downregulated – miR-16-5p, miR-1-3p, miR-291a-3p and miR-27a-3p – and 4 miRNAs are upregulated – miR-150-5p and miR-451a – the most statistically significant. The main canonical pathways affected in the CML-CP include molecular mechanisms of cancer, CML signaling, PTEN signaling, TP53 signaling, PI3K-AKT and MAPK pathways. The main cellular and molecular functions involved in this pathogenesis are related to oncogenesis. The results obtained showed the complexity of CML and suggested that these miRNAs deregulated play a central role in this neoplasia. This research may allows better understanding of molecular behavior of this disease and maybe useful for possible monitoring CML treatment and prognostic biomarkers identification.